2018
DOI: 10.1073/pnas.1719760115
|View full text |Cite
|
Sign up to set email alerts
|

Polo-like kinase 4 inhibition produces polyploidy and apoptotic death of lung cancers

Abstract: Polo-like kinase 4 (PLK4) is a serine/threonine kinase regulating centriole duplication. CFI-400945 is a highly selective PLK4 inhibitor that deregulates centriole duplication, causing mitotic defects and death of aneuploid cancers. Prior work was substantially extended by showing CFI-400945 causes polyploidy, growth inhibition, and apoptotic death of murine and human lung cancer cells, despite expression of mutated or p53. Analysis of DNA content by propidium iodide (PI) staining revealed cells with>4N DNA co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 48 publications
3
69
1
Order By: Relevance
“…in neuroblastoma cells, downregulation of PlK4 could also dramatically increase the rate of apoptosis and lead to an inhibition of cell migratory and invasive abilities (28). additionally, apoptotic death occurred in lung cancer cells after treatment with cFi-400945, a PlK4 inhibitor (29). in the present study, the expression of PlK4 was downregulated in lPS-induced apoptosis and reversed by Syra treatment.…”
Section: Discussionsupporting
confidence: 57%
“…in neuroblastoma cells, downregulation of PlK4 could also dramatically increase the rate of apoptosis and lead to an inhibition of cell migratory and invasive abilities (28). additionally, apoptotic death occurred in lung cancer cells after treatment with cFi-400945, a PlK4 inhibitor (29). in the present study, the expression of PlK4 was downregulated in lPS-induced apoptosis and reversed by Syra treatment.…”
Section: Discussionsupporting
confidence: 57%
“…In addition, the oncogenic role of PLK4 has been studied in various types of cancer ( 9 - 15 ). The expression of PLK4 has been detected in breast cancer ( 11 , 14 ), lung cancer ( 12 ), neuroblastoma ( 13 ) and prostate cancer ( 15 ); however, its expression pattern differs among various types of cancer. Increased PLK4 expression is correlated with higher rates of metastasis in breast cancer ( 11 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, PLK4 high expression was correlated with unfavorable clinicopathological features in NSCLC patients. Besides, inhibition of PLK4 was previously shown to cause defects in cell mitosis and induce cell death in NSCLC cells via regulating centriole duplication, which implied that PLK4 suppressed cell apoptosis and contributed to tumor growth in NSCLC . Thus, PLK4 was associated with greater tumor size and higher TNM stage in NSCLC patients.…”
Section: Discussionmentioning
confidence: 97%
“…In clinical studies, PLK4 is shown to be associated with higher pathological grade and poor prognosis in glioblastoma patients . As for in lung cancer, PLK4 inhibitor attenuated tumor growth via deregulating centriole duplication, mitotic defects, and deaths of lung cancer cells . Whereas for NSCLC, to be specific, the correlation of PLK4 with tumor development, progression, or prognosis is still unclear.…”
Section: Introductionmentioning
confidence: 99%